How well is hypertension managed in the community? A population-based survey in a Brazilian city - Piccini Roberto X.; Victora Cesar G. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1997)
There is usually little information available on how well hypertensive individuals are managed at the community level. This survey measured the frequency of hypertension in a medium-sized Brazilian city by studying a cluster sample of 1657 adults aged 20-69 years. The 328 hypertensives (19.8%) answered a questionnaire on the knowledge and management of their condition. Two-thirds were aware of their status and more than half were on antihypertensive medication, but only one-third had their blood pressure under control. Physicians failed to advise a large proportion of their patients about the need to lose weight, take exercise, and quit smoking. Although laboratory tests were carried out in most patients, fundoscopy and chest X-rays were performed in fewer than 50%. Continued care by the same physician was the only factor significantly associated with compensated high blood pressure (relative risk for not having continued care = 1.35; 95% CI = 1.02-1.71). High levels of absenteeism, reduction of the work load, and early retirement were found among the individuals with high blood pressure.